Correlation of Interleukin-6 Levels with Clinical Features and Chest X-Ray Imaging in Coronavirus Disease-19 (COVID-19) Patients at Dr. Mohammad Hoesin General Hospital Palembang - Raden Yudistira Dwi Ananda; Nova Kurniati; Harun Hudari; Erial Bahar (HM Publisher, 2022)
Background. COVID-19 infection, both moderate and severe symptoms can cause pneumonia that can be detected on a chest X-ray. Along with the increasing severity of the clinical picture of COVID 19, it can also trigger a cytokine storm, one of which is an increase in Interleukin-6 levels. This study was conducted to see the correlation between IL-6 levels with clinical features and chest radiographs in patients with COVID-19 Methods. This research is a cross-sectional study using an observational analytic. The samples in this study were confirmed COVID-19 patients who were being treated at Dr. Mohammad Hoesin General Hospital, Palembang. A history and physical examination were performed to determine the clinical picture as well as a chest X-ray and IL-6 levels. Results. There were 31 samples of COVID 19 patients. High levels of IL-6 were found in 26 (83.9%) samples. The clinical picture of the patient was dominated by dyspnea as much as 19 (61.3%), fever 16 (5.6%), low O2 saturation 12 (38.4%) and a chest X-ray of pneumonia 26 (83.9%). There was a significant relationship (P<0.05) between IL-6 levels with clinical features and chest X-rays. The R-value on the thorax with pneumonia (0.692), lesion area (0.711) and clinical features with temperature (0.906), respiratory rate (0.706) indicated a strong correlation, while O2 (-0.732) indicated a strong negative correlation. Conclusion. There is a significantly strong correlation between Interleukin 6 levels with clinical features and chest X-rays in patients with COVID-19.